Designing Website-Based E-Learning Application on SMP Kusuma Bangsa Using Framework Codeigniter - Cris Sunray; Yusuf Kurnia (Komunitas Dosen Indonesia, 2020)
The Covid-19 pandemic currently occurring around the world, including Indonesia has had an impact and changes in various areas of daily life. Especially, in the field of education which during the Covid-19 pandemic must make efforts to adapt. Minimizing direct interactions is an important first step to avoiding the spread of covid-19. This is also applied to teaching and learning activities between teachers and students therefore teaching and learning activities are carried out online. Without any doubt, this change creates problems and difficulties in the delivery of material, interactions between teachers and students, etc. However, SMP Kusuma Bangsa is a private school that still implements face-to-face learning system. To solve this problem, the author propose making an online learning system. In order to achieve this, the author intend to create an e-learning application. This e-learning application is based on website created using the Codeigniter framework. To find out the application requirements desired by the user, the author make user needs which will be used as a form of analysis in making e-learning application. After getting the results of user needs, the author complete the e-learning application with 3 user models, admin, teacher, and students, each of them has their own function. Likert scale is used to measure the level of user satisfaction of the e-learning application. Based on the results of the calculation, it can be seen that users as respondents who strongly agree with the statement that the e-learning application are in the good category, it shows the acquisition of 84.1%. Therefore, the e-learning application has helped minimize direct interaction, the application operates well, and the presence of an online exam feature, a conference system using the zoom application, etc make teaching and learning activities at SMP Kusuma Bangsa easier